Comparison Of Islamic Law And Positive Law On Violence In The Name Of Religion In Terrorism Cases - Zarkasih, Muhamad (Universitas Semarang, 2023)
The purpose of this study is to determine the legal regulation of violence in the name of religion that contains elements of radicalism, extremism and terrorism in terms of comparative Islamic law and positive law in Indonesia. Radicalism, extremism and terrorism are like three things that go hand in hand, these three are a frightening specter for most of humanity, especially in the Unitary State of the Republic of Indonesia. This research is a type of normative research. The approach used in this study is a statutory and conceptual approach. The results of the study show that in the perspective of Islamic law, behavior that gives birth to extreme understanding by expressing it through violence in order to maintain its ideology can be considered as al-baghy (rebel). Article 43D paragraph (2) letter f of Law no. 5 of 2018 which explains that what is meant by